The Role of Religiosity in Parenting Young Children - Nicholson, Bonnie C. (Research in the social scientific study of religion, 2006)
Cultural determinants of parenting have received recent empirical attention in the literature, however, religion as it relates to parenting practices has been a relatively neglected subject. Studies that do exist typically report between group differences based on religious affiliation, with conservative Protestants typically reporting reliance on corporal punishment. This study investigated within group differences on the role of religiosity in parenting, conceptualizing religiosity in terms of orientation, fundamentalism, and quest. Results suggest that greater incidence of verbal and corporal punishment is related to more fundamentalist beliefs. An intrinsic religious orientation was associated with greater use of positive, nurturing behaviors. Results of the study lend support to the importance of using more complex models of religiosity in determining the impact of this cultural variable on parenting.